Giant degenerative subserous leiomyoma simulating an ovarian cyst, a diagnostic conundrum: a case report - Kapur, Anuradha; Naik, Sonia; Maiti, Saswati; Pandya, Unnati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Leiomyomas are benign tumours of uterus and classified by their location in the uterus- submucosal, intramural, subserous. Uterine leiomyoma can have variable presentations. Pedunculated big subserous fibroids may outgrow their blood supply, undergo degenerative changes and may present as an ovarian mass. We would like to present a case of such variant which presented as a huge ovarian multiloculated cyst on MRI, but final diagnosis after histopathological examination concluded it to be leiomyoma with secondary degenerative changes. Giant degenerative fibroid might present as an ovarian mass which poses challenge in diagnostic course. This may confound with complex ovarian cyst on radiological modalities. Diagnostic certainty can be achieved only by skilful intraoperative examination and histopathology.